Density scaling of phantom materials for a 3D dose verification system. (21st May 2018) - Tani, Kensuke; Fujita, Yukio; Wakita, Akihisa; Miyasaka, Ryohei; Uehara, Ryuzo; Kodama, Takumi; Suzuki, Yuya; Aikawa, Ako; Mizuno, Norifumi; Kawamori, Jiro; Saitoh, Hidetoshi
Abstract: In this study, the optimum density scaling factors of phantom materials for a commercially available three‐dimensional (3D) dose verification system (Delta4) were investigated in order to improve the accuracy of the calculated dose distributions in the phantom materials. At field sizes of 10 × 10 and 5 × 5 cm 2 with the same geometry, tissue‐phantom ratios ( TPR s) in water, polymethyl methacrylate (PMMA), and Plastic Water Diagnostic Therapy (PWDT) were measured, and TPR s in various density scaling factors of water were calculated by Monte Carlo simulation, Adaptive Convolve (AdC, Pinnacle 3 ), Collapsed Cone Convolution (CCC, RayStation), and AcurosXB (AXB, Eclipse). Effective linear attenuation coefficients ( μ eff ) were obtained from the TPR s. The ratios of μ eff in phantom and water (( μ eff )pl, water ) were compared between the measurements and calculations. For each phantom material, the density scaling factor proposed in this study ( DSF ) was set to be the value providing a match between the calculated and measured ( μ eff )pl, water . The optimum density scaling factor was verified through the comparison of the dose distributions measured by Delta4 and calculated with three different density scaling factors: the nominal physical density (PD), nominal relative electron density (ED), and DSF . Three plans were used for the verifications: a static field of 10 × 10 cm 2 and two intensity modulated radiation therapy (IMRT) treatment plans. DSF were determined to be 1.13 for PMMA and 0.98 for PWDT. DSF for PMMA showed good agreement for AdC and CCC with 6 MV x ray, and AdC for 10 MV x ray. DSF for PWDT showed good agreement regardless of the dose calculation algorithms and x‐ray energy. DSF can be considered one of the references for the density scaling factor of Delta4 phantom materials and may help improve the accuracy of the IMRT dose verification using Delta4.